Innovation in teaching for training in clinical reasoning of students of Speech and Language Therapy Degree - Calleja-Reina, Marina; Luque-Liñán, María Luisa; Rodríguez-Santos, José Miguel; Ferrer-Urbano, Francisco Javier; León Carrión, José (My University, 2020)
A challenge in higher education for the Speech and Language Therapy Degree is the training in clinical reasoning skills. Speech and Language Therapy students' competencies are progressively developed by transferring and improving the knowledge they acquire in several subjects by applying it to different clinical situations in an integrated and repeated way. Usually, curricula do not include a systematic method for training to solve clinical problems. In this framework, the authors have created the computer-based Language Assessment Training System (LATS) tool. This tool is a clinical reasoning training system for the diagnosis of virtual cases with language problems. LATS tool has been developed and funded by different Innovation Projects of the University of Málaga (PIE 10-12, PIE 13-15, PIE 17-19, PIE 19-21). Aim: This work aims to show the usefulness of LATS in the training of clinical reasoning skills for students of Speech and Language Therapy degree. Method: LATS has been used with 3rd and 4th-year Speech and Language Therapy students at the University of Málaga. Results: Analysis of student performance using LATS shows that a) repeated use of LATS improves student performance, b) students achieve the basic principles of clinical reasoning when trained with the LATS tool. Conclusions: LATS tool is a useful tool to develop and assess the clinical diagnostic skills of Speech and Language Therapy students.
Keywords: Lenguaje - Trastornos; Logopedia - Estudio y enseñanza; Logopedia - Estudio y enseñanza - Innovaciones tecnológicas; Training; Clinical reasoning; Speech and Language Therapy; Clinical competence training; Virtual cases; Speech therapy